2017 Ieee Sensors 2017
DOI: 10.1109/icsens.2017.8234222
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of supervised classification algorithms for human activity recognition with inertial sensors

Abstract: Abstract-We report first results on developing smart sensor systems for the automatic and frequent collection of animal weight and gait data, under the hostile conditions of a livestock farm. The novelty in our approach is to sense frequently the animals' floor contact, in suitably chosen locations, under natural and unobtrusive conditions. We demonstrate a pilot low profile rubberized mat sensor heads, delivering a large number of plastic optical fiber transmission measurements taken frequently from individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…To place our results in context Table I summaries the performance of other classification techniques when applied to the same data set as used in this paper, and to previous LSTM models. Our proposed LSTM+BN that processes featureless raw signals achieves 92% overall classification accuracy which is slightly lower than the Support Vector Machine (SVM) method in [14] which used handcrafted features to achieve 93.4% accuracy. This compromise in accuracy can be discounted by the fact that the LSTM classification is more generalized and capable detecting activities that have long term dependence which is not the case for SVM.…”
Section: Comparison With Other Approachesmentioning
confidence: 90%
See 1 more Smart Citation
“…To place our results in context Table I summaries the performance of other classification techniques when applied to the same data set as used in this paper, and to previous LSTM models. Our proposed LSTM+BN that processes featureless raw signals achieves 92% overall classification accuracy which is slightly lower than the Support Vector Machine (SVM) method in [14] which used handcrafted features to achieve 93.4% accuracy. This compromise in accuracy can be discounted by the fact that the LSTM classification is more generalized and capable detecting activities that have long term dependence which is not the case for SVM.…”
Section: Comparison With Other Approachesmentioning
confidence: 90%
“…To evaluate the performance of the model, we processed the time series data from a waist mounted inertial sensor recorded at 50 Hz sampling frequency containing both accelerometer and gyroscope measurements. Data for 20 subjects is present, described in detail in [14]. The dataset contains six everyday activities: 0-walk on level surface; 1-walk upstairs; 2-walk downstairs; 3-sitting; 4-standing; 5-lying.…”
Section: B Dataset Preparationmentioning
confidence: 99%
“…Rodriguez et al [23] reported BioHarness and smartphone based activity recognition using decision tree for the classification. Zebin et al [24] conducted the comparison between different HAR algorithms for the inertial sensor data. Tang and Sazonov [9] compared the ANN and SVM classification algorithms for the smart shoe.…”
Section: Related Workmentioning
confidence: 99%
“…We analyse two datasets, henceforth Dataset 1 and Dataset 2. Dataset 1 analysed in [19], contained 661056 observations from 20 participants on activity labels collected at 50 Hz sampling frequency. Six labelled activities were encoded: 0-walk on level surface; 1-walk upstairs; 2-walk downstairs; 3-sitting; 4-standing; 5-lying.…”
Section: A Data Collectionmentioning
confidence: 99%